Assessment of the Attitude of the Youth Towards Christianity in Asuret Parish, Soroti Diocese - Paul Ocola (Uganda Christian University, 2025)
The study assessed the attitude of the youth towards Christianity in Asuret parish, Soroti diocese. The study was guided by the following objectives: to establish the societal factors that affect youths’ attitudes towards Christianity in Asuret parish, to identify the individual factors that affect youth’s attitudes towards Christian faith in Asuret parish and to assess the role of the church in addressing the youths ‘attitude towards Christianity in Asuret parish. The study used a descriptive survey research design. The researcher adopted a qualitative approach. The researcher conducted interviews where the researcher asked questions based on the objectives posed to the respondents and their answers were recorded. The results showed a moderate attitude of youth towards Christianity among the youth of Asuret parish. It established that the youth shunned- away from the church due to influence of alcohol and drugs, expensive weddings that made them to take the church as place of luxury. Furthermore, Christianity did not allow the youth freedom to do certain things like marrying many wives, betting and going for discos. However, the positive attitude of the youth towards Christianity was influenced by cultural and social norms and education levels, fellowships and crusades, mental health awareness and faith based support activities in sub parishes of Asuret parish. It was concluded that the general attitude of the youth towards Christianity at Asuret parish was moderate and the clergy and the entire church leadership in Asuret parish were implementing number of activities so as to increase the levels of youth participation in church activities.
Undergraduate